2001
DOI: 10.1046/j.1464-5491.2001.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus in the last trimester – a feature of maternal iron excess?

Abstract: The results suggest an association between increased iron stores and glucose intolerance at the third trimester in non-anaemic women. The role of iron excess in the pathogenesis of GDM needs to be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
99
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 37 publications
4
99
1
2
Order By: Relevance
“…In the apparently healthy general population, serum levels of ferritin were also positively correlated with baseline serum glucose and with the area under the curve for glucose during the glucose oral tolerance test (20,21). In gestational diabetes, both BMI and serum ferritin levels were found to be independent predictors of 2-h glucose during an oral glucose tolerance test (8,9). Ferritin levels also correlated with diastolic arterial blood pressure, even after adjustment for BMI.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In the apparently healthy general population, serum levels of ferritin were also positively correlated with baseline serum glucose and with the area under the curve for glucose during the glucose oral tolerance test (20,21). In gestational diabetes, both BMI and serum ferritin levels were found to be independent predictors of 2-h glucose during an oral glucose tolerance test (8,9). Ferritin levels also correlated with diastolic arterial blood pressure, even after adjustment for BMI.…”
mentioning
confidence: 89%
“…In the general population, body iron stores are positively associated with the development of glucose intolerance, type 2 diabetes (1-7), and gestational diabetes (8,9). Among U.S. adults, men with newly diagnosed diabetes had an odds ratio (OR) of 4.94 (95% confidence interval [CI] 3.05-8.01) and women had an OR of 3.61 (2.01-6.48) of having elevated ferritin concentrations (6).…”
mentioning
confidence: 99%
“…Several studies have suggested a possible link between high body iron stores and metabolic parameters (9 -13) (serum insulin and glucose) as well as hyp e r t e n s i o n ( 9 , 1 4 ) , d y s l i p i d e m i a (9,15,16), and obesity (9,17). In addition, epidemiological studies have reported an association between high iron stores and increased risk of cardiovascular disease (18), metabolic syndrome (10,12,19), gestational diabetes (20,21), and type 2 diabetes (22)(23)(24)(25)(26)(27). The major source of body iron is derived from the diet.…”
mentioning
confidence: 99%
“…risk of Type 2 diabetes [1,2,3,4,5]. In addition, low iron status or iron depletion is associated with better insulin action and metabolic control in healthy individuals and Type 2 diabetic patients [6,7,8].…”
mentioning
confidence: 99%